Spatial Modeling of Torrential Hazards in the Al-Ratka Valley Basin in the Western Anbar Plateau - Awrad Imad Shehab; Dr Ahmed Falih Fayyad (Migration Letters, 2023)
Objectives: The study focused on spatial hydrological modeling of the flood hazards in AL-Ratka Valley. In the western region of Iraq, more particularly in the Al-Anbar Governorate, can be found find the Al-Ratka Valley. The valley occupies an area of 7134 km2, forming a natural unit. There are six secondary basins in all, and each one is unique in terms of hydrological features. Geology, elevation, and slope characteristics. Methods: were taken into account as part of the study’s natural features. The digital data obtained from topographic maps, aerial photographs, satellite visuals, and Geographic Information Systems (GIS) programs were relied upon. A set of important coefficients were used when studying water basins using Snyder’s model, a number of significant coefficients were employed to examine water basins. This will establish how much of a hazards of flooding the Al-Ratka Valley and its auxiliary basins are. Results: The Ratka Valley basin has gained an important position due to its large area, which provides the opportunity for its investment and sustainability within the northern desert in the Western Plateau. The valley basin represents a natural unit with an area of (7134) km2. The basin consists of six secondary basins: (Al-Aghri, Al-Ajraman, Akash, Malasi, and Al-Awja). The surface of the study area was characterized by an elevation of (835) meters above sea level, while the lowest elevation reached (257) meters above sea level. It is clear through the use of Young’s classification of slope that the region varies in slope between semi-lands. Flat lands (59%) occupied the largest area of the region, and steep lands amounted to (2.5%). Conclusions: According to the study, torrential torrents are hazards in this area. Between different basins, there are differences in the severity. The (Ajrman) basin was discovered to be at a low- hazard torrential level. The basins (Akash, Al-Awja, and the main basin) are situated in an somewhat hazards area of torrential rain. The Al-Aghari, Malsi, and Al-Ratka secondary basins are situated in an area with a high hazard of torrential rains.